Health Status Monitoring of Cuplock Scaffold Joint Connection Based on Wavelet Packet Analysis - Liuyu Zhang; Chenyu Wang; Gangbing Song (Shock and Vibration)
The cuplock scaffolds are widely used as a temporary facility in the bridge and other constructions. The looseness of cuplock scaffold connection plays a significant role in the stability of the structure. Contemporary structural health monitoring method is reviewed in this paper at first, and then we proposed wavelet packet analysis based method. In order to detect the looseness of cuplock connection, three stress PZTs and three shear PZTs used as transducers are mounted onto vertical bar and cross bars of cuplok scaffold. Wavelet packet analysis is applied to analyze the transmitted signal energy between two PZTs through cuplok connection. Experimental results show that shear PZT has better performance than stress PZT to be used as actuator and sensor for the wavelet packet analysis based structural health monitoring. Besides, a sensor looseness index matrix (SLIM) is derived to indicate the looseness of the cuplock connection. The experimental results show that looseness index increases as the connection gets loose.